Dampak Penggunaan Metode Content-Based Instruction terhadap Kemampuan Penggunaan Kosa Kata Bahasa Arab bagi Siswa SMAN 1 Pandeglang - Putri Aulia; Hannanah Mukhtar Thabrani; Ahmad Faroji; Mufrodi, Mufrodi (Lembaga Pengembangan Kinerja Dosen, 2026)
Content-Based Instruction learning is an approach that integrates language learning with materials or topics that are relevant to students’ daily lives. At SMAN 1 Pandeglang, students’ mastery of Arabic vocabulary is still considered less effective because the learning process still uses conventional methods, causing students’ learning interest to be relatively low. This study aims to determine the effect of using the Content-Based Instruction method on students’ Arabic vocabulary mastery. The research employed a quantitative method with a true experimental design, specifically a pretest–posttest control group design. The subjects of this study consisted of 50 students divided into two classes, namely the experimental class and the control class. Data collection techniques were carried out through tests (pretest and posttest) and questionnaires covering five aspects: vocabulary application, vocabulary mastery, ease of understanding the material, participation, and students’ perceptions of the learning process. The results of the study indicate that the use of the Content-Based Instruction method has a significant effect on improving students’ Arabic vocabulary mastery. Therefore, the Content-Based Instruction method can be used as an alternative learning approach that is more effective than conventional methods.